ANALYSIS OF PROFIT AND COST OF SALE IN THE BUSINESS OF MAKING LIQUID SOAP IN AN EFFORT TO IMPROVE THE ECONOMY FAMILY AT DISTRICT TEMBALANG SEMARANG - FAUZI, IRSAL (Jurnal Bakti Humaniora, 2021)
Friendly environmentally liquid soap is one product that supports one of the goals of the permaculture concept. Cost production have the benefit effects and positive impact for social and environmental. This community service program introduces products and how to produce environmentally friendly liquid soap as well as providing insight into profit analysis and cost of goods manufactured through guidance in the form of discussions, presentations and hands-on practice.